2002
DOI: 10.1111/j.1749-6632.2002.tb04418.x
|View full text |Cite
|
Sign up to set email alerts
|

The Medical Management of Cushing's Syndrome

Abstract: Cushing's syndrome results from prolonged exposure to excessive circulating glucocorticosteroids, and is associated with significant morbidity and mortality. While the treatment of choice in most patients is surgical, the metabolic consequences of the syndrome, including increased tissue fragility, poor wound healing, hypertension, and diabetes mellitus, increase the risks of such surgery. The hypercortisolemia and its sequelae can be efficiently reversed using medical therapy, either as a temporary measure pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 95 publications
0
63
0
1
Order By: Relevance
“…For example, Cushing's syndrome, sleeping disorders, work stress and schizophrenia [30][31][32][33] appeared to be associated with an increased level of cortisol and also with an increased risk of type 2 diabetes and insulin resistance, although studies on sleep disorders showed inconsistent results regarding risk of diabetes [33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Cushing's syndrome, sleeping disorders, work stress and schizophrenia [30][31][32][33] appeared to be associated with an increased level of cortisol and also with an increased risk of type 2 diabetes and insulin resistance, although studies on sleep disorders showed inconsistent results regarding risk of diabetes [33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…There are reports that suggest with high dose bromocriptine (40 mg/day) there may be clinical improvement in up to 50% of patients but others have found response rate of only 1-2% in the long term (49,50). Potential side effects of bromocriptine include nasal congestion, nausea, postural hypotension, headaches and hallucination.…”
Section: Dopamine Agonistsmentioning
confidence: 99%
“…There are several treatment aims for medical therapy in CS (Table 3; Morris & Grossman 2002, Feelders et al 2010c. Medical treatment can be indicated because of acute complications of CS like acute psychosis, severe hypertension, and opportunistic infections.…”
Section: Indications For Medical Therapymentioning
confidence: 99%